The effect of the great Kermanshah earthquake on the tuberculosis infection trend: interrupted time series analysis - Ehsan Mardani-Talaee; Yahya Salimi; Fatemeh Heydarpour; Mitra Darbandi; Gholamreza Abdoli (BMC Infectious Diseases)
Abstract Objectives Tuberculosis (TB) presents a substantial danger to populations experiencing crises like earthquakes. This study aims to explore the effect of the Kermanshah earthquake on the trend of TB. Methods This cross-sectional study examined tuberculosis data from 2009 to 2020, using monthly diagnoses. Data was collected from the TB research office and registration system. The study employed interrupted time series (ITS) analysis to assess both the immediate and long-term impacts of the earthquake on TB cases. Results In Sarpol-e Zahab, TB cases initially surged after the earthquake, indicating an immediate effect, but then significantly declined compared to pre-earthquake levels, reflecting an effect over time (β0 = 1.39, β1=-0.004, β2 = 0.11 and β3=-0.01, P = 0.001 and Post-intervention linear trend= -0.015, P < 0.001). In Ghasr-e Shirin, the average number of TB cases prior to the earthquake was estimated at 0.58 cases, with a significant monthly decrease of 0.005 cases leading up to the earthquake (P = 0.001). There was no significant immediate change in TB cases during the first month after the earthquake (β2 = 0.008, P = 0.680). Post-earthquake, TB cases dramatically increased (β3 = 0.008, P = 0.001). The monthly trend of TB cases rose significantly by 0.002 (P = 0.001), indicating an effect over time. In Salas-e Babajani, there was no immediate change in TB cases, but there was a significant long-term decline compared to the period before the earthquake (P = 0.001). Conclusions Earthquake is one of the natural crises that provide the conditions for the increase of TB. Local health policymakers must make plans in these areas to contain TB after the earthquake.